If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -16 = 32 Reorder the terms: -16 + 4m = 32 Solving -16 + 4m = 32 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 4m = 32 + 16 Combine like terms: -16 + 16 = 0 0 + 4m = 32 + 16 4m = 32 + 16 Combine like terms: 32 + 16 = 48 4m = 48 Divide each side by '4'. m = 12 Simplifying m = 12
| 2(x-7)=15+4x | | 2x-7=15+4x | | 17-3a=5a+-16a | | x^3+3x^2=125 | | 2a^2+14a+24=0 | | 9.8*0.5*4= | | 10x-13=6x+1 | | 2x+9rtx-5=0 | | x^2+20x+7=0 | | 3(x+2)=x+(x+2)+(3x-1) | | X+X=(30*3*2) | | -6-3(2k+4)=-8 | | 4(2x-3)=-5 | | 3x(2x-3)=0 | | 6x^2+4x-54=0 | | 4x+6x=10x | | p+p+p+p= | | 19=3x | | X(4X+5)-3=0 | | X(4X+5)-3=5 | | 4(-4t^2+27-45)=0 | | 5x-3=-1 | | 9x^2+60x+100=0 | | 6(3-a)+7(3a+2)-4(a+5)= | | 9x-5x+8x-6x= | | (2+y)+y=4 | | 15-13x-20x^2=0 | | -X+2y=1 | | 5+(2-3)-(6-4)+7= | | 2x-10=48 | | 14+(-3)-(-6)+8= | | 7(2)+7y=-10 |